PLURAL FORMS OF NOUNS IN ENGLISH AND UZBEK (Ustozlar uchun, 2026)
This article provides a detailed analysis of the grammatical characteristics of plural nouns and explains the rules and mechanisms involved in their formation. It examines how plural forms are constructed in English, highlighting both regular and irregular patterns. The discussion is supported by clear, well-chosen examples that help illustrate each rule and make the concepts easier to understand for learners.